Critical firing and misfiring boundary in a spark ignition methanol engine during cold start based on single cycle fuel injection. (September 2015) - Li, Zhaohui; Gong, Changming; Qu, Xiang; Liu, Fenghua; Sun, Jingzhen; Wang, Kang; Li, Yufeng
Abstract: The influence of the mass of methanol injected per cycle, ambient temperature, injection and ignition timing, preheating methods, and supplying additional liquefied petroleum gas (LPG) injection into the intake manifold on the critical firing and misfiring boundary of an electronically injection controlled spark ignition (SI) methanol engine during cold start were investigated experimentally based on a single cycle fuel injection with cycle-by-cycle control strategy. The critical firing and misfiring boundary was restricted by all parameters. For ambient temperatures below 16 °C, methanol engines must use auxiliary start-aids during cold start. Optimal control of the methanol injection and ignition timing can realize ideal next cycle firing combustion after injection. Resistance wire and glow plug preheating can provide critical firing down to ambient temperatures of 5 °C and 0 °C, respectively. Using an additional LPG injection into the intake manifold can provide critical firing down to an ambient temperature of −13 °C during cold start. As the ambient temperature decreases, the optimal angle difference between methanol injection timing and LPG injection timing for critical firing of a methanol engine increases rapidly during cold start. Highlights: A single cycle fuel injection and cycle-by-cycle control strategy are used to study. In-cylinder pressure and instantaneous speed were used to determine firing boundary. For the ambient temperatures below 16 °C, an auxiliary start-aids must be used. A preheating and additional LPG were used to expand critical firing boundary. Additional LPG can result in critical firing down to ambient temperature of −13 °C.